The Association of Resident Communication Abilities and Antibiotic Use in Long‐Term Care. Issue 6 (28th January 2019) - Saxena, Farah E.; Bronskill, Susan E.; Brown, Kevin A.; Campitelli, Michael A.; Garber, Gary; Langford, Bradley; Maxwell, Colleen J.; McCormack, Daniel; Schwartz, Kevin L.; Daneman, Nick
Abstract : OBJECTIVES: To determine whether decreased communication ability among long‐term care residents is associated with increased antibiotic exposure. DESIGN: Retrospective cohort study. SETTING: All long‐term care homes in Ontario, Canada. PARTICIPANTS: All adults aged 66 years or older residing in long‐term care and undergoing a full assessment between January 1 and December 31, 2016 (N = 87, 947). MEASUREMENTS: Data were obtained from linkable, population‐wide administrative data sets. Residents were identified, and characteristics were abstracted from the Resident Assessment Instrument Minimum Dataset version 2.0. The primary predictors of interest were residents' ability to make themselves understood and ability to understand others. The primary outcome was antibiotic days of treatment per 1000 resident days in the 90 days following assessment (obtained from the Ontario Drug Benefits Database). RESULTS: Those who were sometimes/rarely/never able to make themselves understood received 50.7 antibiotic days per 1000 person‐days of follow‐up, compared to 62.1 received by those who were able to make themselves understood. Those who were sometimes/rarely/never able to understand others received 50.0 antibiotic days per 1000 person‐days of follow‐up, compared to 61.4 by those who were able to understand others. Multivariable Poisson regression, accounting for resident characteristics, confirmed that compared to those with highest levels of communication ability, those who could sometimes/rarely/never make themselves understood had significantly fewer days on antibiotics (rate ratio [RR] = 0.76; confidence interval [95% CI] = 0.73‐0.79) as did those who could sometimes/rarely/never understand others (RR = 0.76; 95% CI = 0.74‐0.79). CONCLUSION: Poor resident communication ability is not a driver of antibiotic overuse in long‐term care. In fact, lower ability to understand others and/or be understood by others is associated with less antibiotic exposure. Further work is needed to optimize antibiotic use in long‐term care residents across the entire spectrum of communication skills.